The Coexistence of Gonadal Dysgenesis With Mayer-rokitansky-küster-hauser Syndrome, and Dandy-Walker Variant - Shahin Koohmanaee (Guilan University of Medical Sciences, 2021)
Background: Gonadal dysgenesis, the most common cause of primary amenorrhea, is characterized by absent or underdeveloped ovaries. Although the coexistence of gonadal dysgenesis and Mayer-Rokitansky-Küster-Hauser (MRKH) has been reported, it is still quite infrequent. To the extent that authors searched, just one study reported the association between Rokitansky sequence and Dandy-Walker malformation. Clinical Presentation and Intervention: We aimed to report a case with gonadal dysgenesis, MRKH, and the Dandy-Walker variant. In this care report, the authors reported a 15-year-old girl with primary amenorrhea and underdeveloped secondary sexual properties. Her karyotype was 46, XX. The abdominopelvic MRI without contrast demonstrated bilateral ovarian agenesis and no uterus or cervix. Vagina was normal in length. Brain MRI was consistent with the Dandy-Walker variant. Conclusion: Although some affected chromosomal regions have been identified, further genetic analyses should be performed to elucidate the probable association between these anomalies.